OLD HABITS DIE HARD ‒ THE SOUTH AFRICAN REVENUE SERVICE’S INABILITY TO COMPLY WITH ITS OWN LEGISLATION Sip Project Managers (Pty) Ltd v C:SARS Case number: 11521/2020 Gauteng Division, Pretoria (30 April 2020) - Carika Fritz (Obiter, 2021)
The South African Revenue Service (SARS) has identified third-party appointment as an important weapon in its tax-collection arsenal. In terms of section 179(1) of the Tax Administration Act 28 of 2011 (TAA), SARS is permitted to issue a third-party appointment notice in terms whereof a third party becomes liable for the taxpayer’s tax debt in instances where the third party holds (or will hold) money on behalf of or due to the taxpayer. Although the usefulness of the appointment of a third party from a collection perspective is apparent, it remains important to ensure that certain built-in measures are in place to ensure that SARS does not use this power in an overzealous manner and that taxpayers’ rights are respected.This case note reflects on the case of Sip Project Managers (Pty) Ltd v C: SARS (Case number: 11521/2020 Gauteng Division, Pretoria (30 April 2020)), where section 179(5) of the TAA was considered. The SIP Project Managers case is important because it provides some perspective on this relatively new insertion in the TAA. In the first part of this case note, the facts of the case and the judgment are provided. In the next part, the judgment is analysed by considering the consequences of SARS’s failure to adhere to peremptory wording and by contemplating whether the tax debt must be “due and payable” before a notice in terms of section 179(5) of the TAA can be delivered. Thereafter, some conclusions are drawn.